Аркасівська перлина (сторінки історії села Стара Богданівка) - Тригуб, О. (Краєзнавство, 2013)
Стаття розкриває історію села Стара Богданівка, колишнього маєтку відомої на Миколаївщині родини Аркасів. Саме у цьому селі народився відомий композитор, культурний і громадський діяч, історик Микола Аркас. Статья раскрывает историю села Старая Богдановка, бывшего имения известной на Николаевщине семьи Аркасов. Именно в этом селе родился известный композитор, культурный и общественный деятель, историк Николай Аркас. The article reveals the history of the village of Stara Bogdanivka, the former estate of the famous family of Arcas in Mykolayiv. It was in this village was born the famous composer, cultural and social activist, historian Mykola Arkas.